2021
DOI: 10.1016/j.breast.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy associated breast cancer (PABC): Report from a gestational cancer registry from a tertiary cancer care centre, India

Abstract: Background: Pregnancy associated breast cancer (PABC) is a rare entity and defined as breast cancer diagnosed during pregnancy or one-year post-partum. There is sparse data especially from low and middle-income countries (LMIC) and merits exploration. Methods: The study (2013e2020) evaluated demographics, treatment patterns and outcomes of PABC. Results: There were 104 patients, median age of 31 years; 43 (41%) had triple-negative disease, 31(29.8%) had hormone-receptor (HR) positive and HER2 negative, 14 (13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
(50 reference statements)
2
21
0
Order By: Relevance
“…This multi-drug chemotherapy was well tolerated with grade-III toxicity similar to that reported in major studies despite the high prevalence of malnutrition among multiparous Indian women [31e34]. However, caution must be exercised to avoid intensification of treatment just based on the age as suggested by the international guidelines [1,9].The outcomes of the small subset of PABC patients in our study were similar to that seen in a larger study of 104 PABC patients published from our institute had showed comparable stage matched OS and DFS with non PABC patients [35].…”
Section: Discussionsupporting
confidence: 88%
“…This multi-drug chemotherapy was well tolerated with grade-III toxicity similar to that reported in major studies despite the high prevalence of malnutrition among multiparous Indian women [31e34]. However, caution must be exercised to avoid intensification of treatment just based on the age as suggested by the international guidelines [1,9].The outcomes of the small subset of PABC patients in our study were similar to that seen in a larger study of 104 PABC patients published from our institute had showed comparable stage matched OS and DFS with non PABC patients [35].…”
Section: Discussionsupporting
confidence: 88%
“…In a retrospective study of 142 women with PABC, performed by Wang et al [ 55 ], five-year overall survival (OS) and disease-free survival (DFS) rates were 76.8% and 63.5%, respectively, with T stage, N stage, and HER2 status, distinguished by univariate analysis, being significant prognostic factors for both OS and DFS. Bajpai et al [ 56 ] further demonstrated that the 3 year event-free survival (EFS) was significantly different among PABC patients with early-stage, locally advanced and metastatic breast cancer, estimated at 82% (95% CI: 65.2–100), 56% (95% CI: 42–75.6%) and 24% (95% CI: 10.1–58.5%), respectively.…”
Section: Maternal Adverse Outcomesmentioning
confidence: 99%
“…PABC is also associated with an increased risk of early postnatal complications when compared to normal pregnancies, which are mainly caused by prematurity. Early neonatal complications include neonatal death, neonatal intensive care unit (NICU) admission, hematologic disturbances (especially neonatal anemia), low birth weight and other prematurity-related disorders (respiratory distress syndrome, metabolic disturbances, sepsis, infant jaundice, and necrotizing enterocolitis) [ 56 , 84 , 85 , 86 ], while low Apgar scores after birth are also more common in the neonates of PABC patients [ 84 , 87 ]. Finally, in addition to the aforementioned risk of placental metastasis from PABC, fetal metastasis can theoretically occur too, with extremely poor anticipated prognosis, however, there have been no reported cases of distant metastasis to the fetus.…”
Section: Obstetrical Fetal and Neonatal Adverse Outcomesmentioning
confidence: 99%
“…63 Pregnancy-associated BC is challenging; however, stage- and biology-matched outcomes are largely comparable if appropriately managed. 64…”
Section: Multidisciplinary Management Of Bcmentioning
confidence: 99%